CHITINASE AND CHITINOLYTIC MICROORGANISM : ISOLATION, CHARACTERIZATION AND POTENTIAL - Nuniek Herdyastuti; Tri Joko Raharjo; Mudasir Mudasir; Sabirin Matsjeh (Universitas Gadjah Mada, 2009)
Chitinase is enzyme that hydrolyzes chitin, a polimer of b-1,4-N-Acetilglucosamine which is the most abundant natural resource after cellulose. Chitinolytic microorganism can be found in environment like soil and water that contain chitin, or in extreme environment which is known as thermofilic microorganism. Chitinolytic microorganism is identified by recognizing the morphological and physiological properties based on Bergey's Manual of Systematic Bacteriology. The sequence data of the 16S rRNA genes is determinated in the GeneBank nucleotide sequence database. Chitinase activity can be qualitatively determined from the clearance zone around the colony formed in agar medium containing colloidal chitin. Chitinase can be utilized as biocontrol agent and derivate chitin as the result of chitinase degradation which can be used in the fieltd of health, food, industry and waste management